Antimicrobial Susceptibilities of Coagulase-Negative Staphylococci Isolated from Urinary Infections - Bourgault, Anne-Marie (1983)
The susceptibilities of 107 urinary isolates of coagulase-negative staphylococci to 19 antibiotics was determined by an agar dilution technique. Major differences in the antimicrobial susceptibilities of species of coagulase-negative staphylococci were observed. Staphylococcus epidermidis was more resistant to a wider spectrum of antibiotics than was Staphylococcus saprophyticus.